Physiological evaluation of soybean (Glycine max (L.) Merr.) varieties as influenced by inoculation and sowing date in the Guinea Savanna - Aminu, A.S. (Ahmadu Bello University, 2019)
A field trial was conducted during the 2018 Rainy Season at the Research Field of International Institute of Tropical Agriculture, University farm of Ahmadu Bello University, Zaria at Samaru in the Northern Guinea Savanna and International Institute of Tropical Agriculture Research farm, Kubwa Abuja in the Southern Guinea Savanna of Nigeria. The treatments consisted of four varieties of soybean (TGx 1904-6F, TGx 1951-3F, TGx 1955-4F and Sambaiba), two sowing dates (late June and early July) and two levels of inoculation (inoculation and without inoculation). The treatments were laid out in a Randomized Complete Block Design (RCBD) replicated three times. The result of the study revealed that, the treatments with inoculant had significantly (P< 0.05) higher values for plant height (89.97 cm), effective nodules per plant (72.51%) and shoot dry matter (34.87 cm). Yield parameters such as number of pods per plant, number of seeds per plant, 100-seed weight and grain yield per hectare (2145 Kg ha-1) were also significantly (P< 0.05) increased in plots treated with inoculant. In late June sowing, growth components such as plant height, days to 50% flowering, shoot dry matter, days to 95% maturity and also yield components such as number of pods per plant, number of seeds per plant, number of nodules per plant and grain yield per hectare (2035.7 Kg ha-1) responded significantly (P< 0.05) to sowing date. Among the varieties used, Sambaiba (2240.3 Kg ha-1 of yield) which is an exotic variety outperformed the other local improved varieties in almost all the growth and yield parameters. This was closely followed by TGx 1951-3F variety (2172.18 Kg ha-1 of yield). Significant interaction between variety and inoculation treatments was observed in crop growth rate, number of pods per plant and grain yield per hectare at Samaru where Sambaiba variety in combination with inoculant recorded the highest value. There was also a significant interaction between variety and sowing date treatments on leaf area index (6 WAS) where the sowing of TGx 1904-6F and TGx 1955-4F varieties at late June and early July respectively produced the highest LAI value at Samaru. A significant and positive correlation between soybean grain yield and parameters like plant height, intercepted photosynthetic active radiation, crop growth rate, number of days to 95% maturity, shoot dry matter, harvest index, number of pods per plant and number of seeds per plant was observed. In conclusion, TGx 1951-3F and Sambaiba varieties gave the highest grain yield per hectare at Kubwa and Samaru respectively, application of inoculant and late June sowing gave the highest yield and all the varieties were able to adapt to both ecologies.